2022
DOI: 10.3390/cancers14041068
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphisms of Genes Encoding Catalytic Antioxidant Proteins Modulate the Susceptibility and Progression of Testicular Germ Cell Tumor

Abstract: The simultaneous analysis of redox biomarkers and polymorphisms encoding for regulatory and catalytic antioxidant proteins was performed in order to evaluate their potential role in the development of testicular germ cell tumor (GCT), as well as the progression of the disease. NRF2 (rs6721961), GSTM3 (rs1332018), SOD2 (rs4880) and GPX3 (rs8177412) polymorphisms were assessed in 88 patients with testicular GCT (52 with seminoma) and 88 age-matched controls. The plasma levels of 8-hydroxy-2′-deoxyguanosine (8-OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…In total, 113 patients with testicular masses were treated at the Urology Clinic, University Clinical Centre of Serbia, between the years 2020 and 2021. In accordance with the previously elaborated enrollment process, predefined eligibility criteria were applied to the cohort [ 13 ]. Patients diagnosed with benign scrotal pathology (epidermal cyst, chronic epididymitis, segmental testicular infarction, testicular atrophy, or Leydig cell hyperplasia; n = 12), non-germ-cell testicular tumors (Leydig cell tumor, Sertoli cell tumor, or adenomatoid tumor; n = 7), and non-testicular malignancy (non-Hodgkin lymphoma; n = 1) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 113 patients with testicular masses were treated at the Urology Clinic, University Clinical Centre of Serbia, between the years 2020 and 2021. In accordance with the previously elaborated enrollment process, predefined eligibility criteria were applied to the cohort [ 13 ]. Patients diagnosed with benign scrotal pathology (epidermal cyst, chronic epididymitis, segmental testicular infarction, testicular atrophy, or Leydig cell hyperplasia; n = 12), non-germ-cell testicular tumors (Leydig cell tumor, Sertoli cell tumor, or adenomatoid tumor; n = 7), and non-testicular malignancy (non-Hodgkin lymphoma; n = 1) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have confirmed the relationship between these convenient differential blood cell scores and clinicopathological characteristics, tumor invasiveness, recurrence, and survival in a wide array of malignancies, including urological [ 8 , 11 , 12 ]. However, there is a paucity of information regarding the redox status of testicular cancer patients [ 13 ] and the prognostic relevance of redox biomarkers in such populations. Therefore, the aim of the present study was to address the interplay of systemic inflammatory response and oxidative stress among testicular germ-cell tumor (GCT) patients, and to evaluate the clinical relevance of the preoperative biomarkers of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…TGCT occur in young men, between 15 and 44 years of age, and their incidence has been increasing in the last 30 years [86] and is highly variable in different populations, reporting higher incidences in Caucasian populations than in the African and Asian populations [87]. It has been postulated that the genetic background of each population plays an important role in the susceptibility to TGCT [88]. The global incidence of TGCT is 2.8 per 100,000 male live births [89].…”
Section: Mirnas Expressed In Testicular Germ Cell Tumorsmentioning
confidence: 99%
“…A wide range of factors has been suspected of being associated with the etiopathology of testicular germ cell tumor (GCT), including individual genetic alterations, intensifying the predisposition to cancer development [ 7 ]. Polymorphisms occurring within genes encoding the antioxidant proteins have been assessed in our previous study, investigating the inter-individual susceptibility toward testicular GCT development in patients with presumably altered redox profile [ 31 ]. As reactive species may set an ambient for cancer onset and evolution, the redox status of still very young male individuals could be additionally characterized by perturbations due to reduced antioxidant activities of GSTO isoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…As reactive species may set an ambient for cancer onset and evolution, the redox status of still very young male individuals could be additionally characterized by perturbations due to reduced antioxidant activities of GSTO isoenzymes. Several polymorphisms in the GST omega class have been acknowledged as cancer-risk biomarkers [ 22 , 23 , 24 , 25 ], but, to the best of our knowledge, this is the first study investigating the association of GSTO1 polymorphic expression in relation to testicular tumorigenesis [ 31 , 32 , 33 , 34 , 35 ]. Therefore, the aim of this pilot study was to further define a unique redox profile by determining the individual, combined, haplotype, and cumulative effect of GSTO1 rs4925, GSTO2 rs156697, and GSTO2 rs2297235 genetic variants on the risk for testicular germ cell tumor development.…”
Section: Introductionmentioning
confidence: 99%